Karyotype analysis of Minuartia mesogitana subsp. mesogitana and Minuartia elmalia (Caryophyllaceae, Alsinoideae). - O?uz Yüce (Boletín de la Sociedad Argentina de Botánica, 2016)
Mitotic metaphase chromosomes, karyotypic characters, monoploid karyograms and ideograms of Minuartia mesogitana subsp. mesogitana and Minuartia elmalia were investigated. Analysis of somatic metaphases showed that the chromosome numbers and the karyotype formula of these taxa were 2n = 2x = 24 = 8m + 8sm + 8st for Minuartia mesogitana subsp. mesogitana and 2n = 2x = 32 = 12m + 16sm + 4st for Minuartia elmalia. No satellites were observed in the karyotypes of the taxa. The intrachromosomal and interchromosomal karyotype asymmetries were estimated with Mean Centromeric Asymmetry (MCA) and Coefficient of Variation of Chromosome Length (CVCL).